IFNG Polymorphism (+874 T>A) is not a risk factor for cervical cancer - Ani Melani Maskoen; Herman Susanto; Samsudin Surialaga; Edhyana Sahiratmadja (Universa Medicina, 2013)
INTRODUCTION Cervical cancer cases are rising and many women are infected with human papillomavirus (HPV). Interferon gamma (IFN-ã) is one of the key regulatory cytokines that influence the HPV clearance. The production and the function of IFN-ã may impaired by the defect of the IFNG gene leading to the cervical malignant progression. This study aimed to examine the association between IFNG+874 T>A polymorphism and cervical cancer in women METHODS In a case-control study design, consecutive untreated women with cervical cancer who showed for the first time in Hasan Sadikin Hospital Bandung were enrolled (n=98) and for controls women who came for PAP smear (n = 81). Controls were not matched in ages and ethnicities. DNA extracted from blood was amplified by amplification refractory mutation system - polymerase chain reaction method (ARMS – PCR) to detect IFNG+874 T>A polymorphism. RESULTS The distribution of IFNG genotypes TT, TA and AA for women with cervical cancer who met the inclusion criteria (n= 64) and with negative intraepithelial lesion or malignancy (n=42) were 14.1%, 50.0%, 35.9% and 7.1%, 52.4%, 40.5%, respectively. No significant differences could be observed between both groups (p=0.64). Stratifying the cervical cancer women into a group of squamous cell carcinoma (n = 54) revealed no statistical different. CONCLUSION IFNG +874 T>A polymorphismseems not to contribute in susceptibility to cervical cancer. Identification of other variants in IFNG gene signaling and its role in the development of cervical cancer diseases need to be further examined.